74th American Exhibition. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1982)
Ahearn, John ; Armajani, Siah ; Asher, Michael ; Baldessari, John ; Bell, Larry ; Benglis, Lynda ; Birnbaum, Dara ; Bochner, Mel ; Bosman, Richard ; Brown, Joan ; Burton, Scott ; Dean, Peter ; Ferrer, Rafael ; Goldstein, Jack ; etc.
74th American Exhibition, The Art Institute of Chicago, June 12 - August 1, 1982
boek